Age- and sex-specific reference intervals for trace elements in infants and children: a multi-center study in Lincang, China - Li, Junqiang; Chen, Zhongguo; Zhang, Xuezu; Fu, Zhaobing; Qin, Min (Frontiers in Pediatrics, 2025)
BackgroundWe used an algorithm to determine age- and sex-specific reference intervals (RIs) for copper, zinc, calcium, magnesium, iron, and lead in blood. Data were collected from three health screening centers.MethodsThe data were obtained from the trace element test results of 3933 outpatients aged <18 years at three health examination centers in Lincang City between June 2014 and May 2024. Atomic absorption spectrometry was employed to measure the trace element. Participants were divided into subgroups at 1-year intervals according to age and gender. Decision trees were constructed by the Classification and Regression Tree method to determine the optimal age segmentation point. Harris-Boyd and Lahti methods were used to assess the appropriateness of age segmentation.ResultsAfter the appropriate segmentation points are determined, the refineR algorithm is applied to calculate RIs. After data cleaning, 3933 samples were analyzed for age subgroup partitioning of trace elements from 1 month through 18 years. The difference between the age sub-groups was statistically significant according to the Harris-Boyd method and the Lahti method. Blood copper and calcium levels gradually decreased with months and blood zinc and iron concentration gradually increased with months. After gradually decreasing with months, blood pb levels in boys and girls tended to peak at 15 years and beyond. Blood magnesium levels remained stable.ConclusionsWe have established RIs for six trace elements for children, and the methods we use provide reference for laboratories around the world.